2016
DOI: 10.1177/875687051603500104
|View full text |Cite
|
Sign up to set email alerts
|

Rural Secondary Educators' Perceptions of Their Efficacy in the Inclusive Classroom

Abstract: The purpose of this study was to compare the differences in rural secondary special and general education teachers' perceptions of their efficacy in teaching students in an inclusive classroom. The sample consisted of 148 rural secondary general education and 32 special education teachers. The researchers used an independent-samples t test to determine if there was a difference in the efficacy of student engagement for general and special education teachers. Results indicated there was a significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…The self-efficacy beliefs of a special education teacher are directly related to the improvement of learning outcomes. As a result, they constitute an important factor for the educational context that optimizes teaching effectiveness to help students (Kuronja, Čagran, & Krajnc, 2019;Leggio & Terras, 2019;Levi, Einav, Raskind, Ziv, & Margalit, 2013;Miesera, DeVries, Jungjohann, & Gebhardt, 2019;Peebles & Mendaglio, 2014;Sharma & Sokal, 2016;Shoulders & Krei, 2016). Studies that have examined the conditions for enhancing teacher effectiveness and improving students' academic achievement have found strong correlations between teachers' self-efficacy and behaviour (Gerhardt & Brown, 2006;Kuronja et al, 2019;Miesera, et al, 2019;Peebles & Mendaglio, 2014).…”
Section: Self-efficacy Of Special Education Teachersmentioning
confidence: 99%
“…The self-efficacy beliefs of a special education teacher are directly related to the improvement of learning outcomes. As a result, they constitute an important factor for the educational context that optimizes teaching effectiveness to help students (Kuronja, Čagran, & Krajnc, 2019;Leggio & Terras, 2019;Levi, Einav, Raskind, Ziv, & Margalit, 2013;Miesera, DeVries, Jungjohann, & Gebhardt, 2019;Peebles & Mendaglio, 2014;Sharma & Sokal, 2016;Shoulders & Krei, 2016). Studies that have examined the conditions for enhancing teacher effectiveness and improving students' academic achievement have found strong correlations between teachers' self-efficacy and behaviour (Gerhardt & Brown, 2006;Kuronja et al, 2019;Miesera, et al, 2019;Peebles & Mendaglio, 2014).…”
Section: Self-efficacy Of Special Education Teachersmentioning
confidence: 99%
“…Moreover, resource scarcities also have an adverse effect on the performance of teachers. For example, Shoulders and Krei [23] found that the number of hours spent on teachers’ professional development has a positive impact on the teachers’ ability to engage students. Some authors [8,18,19] have also found that conflict-inducing attitudes in the education sector affect learning outcomes and the psychological well-being of students.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…In implementing inclusive education for young children with autism spectrum disorder (hereafter, ASD), teachers of mainstream classes empowered to apply inclusive practices are more likely to ensure successful learning for these children (Shoulders & Krei, 2016). Despite an increased awareness of ASD in many parts of the world, teachers Can pictorial narration offer a solution to teacher training on the effective inclusion of students with autism spectrum disorder in low-resource settings?…”
Section: Introductionmentioning
confidence: 99%